Assessing δ13C, δ15N and Total Mercury Measures in Epidermal Biopsies From Gray Whales - Lian, Marianne; Castellini, J. Margaret; Miller, Debra; Griff, Brooke; Vertyankin, Vladimir V.; Dupont, Jennifer; Broker, Koen; Godard-Codding, Céline A. J.; O’Hara, Todd M. (Frontiers in Marine Science, 2020)
The gray whale (Eschrichtius robustus) is recognized as two geographically isolated and somewhat genetically distinct populations, with recent evidence showing exchange that questions the degree of isolation. The western gray whale subpopulation is currently listed as critically endangered, as designated by the IUCN, whereas the eastern North Pacific population is listed by the IUCN as “Least Concern.” The International Whaling Commission has stressed the value of studies on feeding ecology and contaminants for the western subpopulation. Our objective was to test for differences among epidermal tissue strata as part of an optimization effort to best use and interpret data from small biopsy samples. Fresh to moderately decomposed full thickness samples of epidermis and dermis were collected from stranded eastern gray whales along the California coast, United States (N: 14), and biopsy samples (N: 10) were collected from free-ranging western gray whales. We determined 13C and 15N stable isotope ratios (δ13C, δ15N); and total Hg concentrations ([THg]) from histologically different strata of epidermal tissue samples from the eastern gray whale population The information from these assessments (stranded whale samples) were directly applied for determining δ13C and δ15N from biopsies collected remotely from free-ranging western gray whales, as well as evaluating [THg]. We found a significant difference in [THg] values between the different strata. This has implications for analyzing Hg, and possibly other elements, from an epidermal biopsy from a free-ranging gray whale, and we recommend identifying which stratum/strata the biopsy represents. There were no significant differences in δ13C and δ15N values between the different strata, making epidermal biopsies from free-ranging gray whales an ideal sampling method to investigate δ13C and δ15N ratios regardless of strata representation.